2021
DOI: 10.3390/cells10051049
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VEGF-Resistant Retinal Diseases: A Review of the Latest Treatment Options

Abstract: Anti-vascular endothelial growth factor (anti-VEGF) therapy currently plays a central role in the treatment of numerous retinal diseases, most notably exudative age-related macular degeneration (eAMD), diabetic retinopathy and retinal vein occlusions. While offering significant functional and anatomic benefits in most patients, there exists a subset of 15–40% of eyes that fail to respond or only partially respond. For these cases, various treatment options have been explored with a range of outcomes. These opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 167 publications
(167 reference statements)
1
69
0
Order By: Relevance
“…Current treatments include the use of anti-VEGF agents, which improve visual acuity in 25–30% of DR patients [ 102 , 107 , 108 ]. Anti-VEGF therapy for DME results in a decrease in fluid leakage and can be sufficient to restore vision in DME patients [ 106 , 109 ]. Laser photocoagulation is also used for treatment of PDR and DME [ 104 ].…”
Section: Neovascular Eye Diseasesmentioning
confidence: 99%
“…Current treatments include the use of anti-VEGF agents, which improve visual acuity in 25–30% of DR patients [ 102 , 107 , 108 ]. Anti-VEGF therapy for DME results in a decrease in fluid leakage and can be sufficient to restore vision in DME patients [ 106 , 109 ]. Laser photocoagulation is also used for treatment of PDR and DME [ 104 ].…”
Section: Neovascular Eye Diseasesmentioning
confidence: 99%
“…However, intense research is being carried out targeting these pathologies using a wide variety of approaches [58][59][60][61][62][63]. Current strategies focus on slowing down or stop the initial triggers (e.g., AREDS supplementation, exercise, eating well, and smoking cessation in dry AMD, and anti-VEGF intraocular injections in wet AMD) [64,65], or focus on relieving the symptoms (e.g., lowering intraocular pressure (IOP) with prostaglandin analogues or beta blockers in glaucoma) [66]. Given the wide expression profile of the eCB system in the neuro-retina, the use of this system as a pharmacological target, particularly the typical and atypical cannabinoid receptors, in the management of these retinal diseases is of great interest.…”
Section: Cannabinoid Receptors In Retinal Diseasesmentioning
confidence: 99%
“… 17 , 18 Steroid injections, laser treatment, and anti-VEGF agents are currently used therapies for most retinal diseases and are selected based on the clinical scenario. 19 The most common route of delivering the macromolecules to the posterior segment requires frequent intravitreal injections that carry a risk of serious adverse effects. 13 , 14 Intravitreal injection of anti-VEGF requires a monthly injection, which can lead to patient discomfort, increase chance of postinjection infections, and related complications.…”
Section: Introductionmentioning
confidence: 99%
“… 20 22 Steroids implants, such as intravitreal triamcinolone (IVTA), Dexamethasone (DEX), and fluocinolone acetonide (FA), are all effective in the treatment of retinal vascular diseases. 19 DEX implants are also effective for the treatment of diabetic retinopathy as an alternative and/or in combination with anti-VEGF therapy. 23 27 Previous studies have shown that DEX intravitreal implants can deliver a sustainable release of macromolecules into the eye, which can help control the severity of diabetic macular edema (DME) and complications after vitrectomy surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation